Communicating About Choices in Transplantation (COACH): Results of a Pilot Test Using Matched Controls. (March 2017) - Traino, Heather M.; West, Stacy M.; Nonterah, Camilla W.; Russell, Jennifer; Yuen, Eva
Introduction: Previous research highlights the difficulties patients with end-stage renal disease awaiting kidney transplant experience while attempting to manage both the logistical and the content-related aspects of discussions about transplantation. This article presents pilot results of the behavioral communication intervention program, Communicating about Choices in Transplantation (COACH), designed to improve transplant candidates' communication about transplantation. Research Questions: As compared to matched controls, increases in knowledge of deceased and living donor transplantation, communication self-efficacy, intentions to hold conversations about transplantation, and self-reported discussion were expected for pilot participants from pre- and postassessment; decreases in conversational difficulties were also posited. Design: Using a nonrandomized quasi-experimental design, we compared transplant knowledge and communication between patients completing a 2-hour COACH session (pilot sample) to a sample of matched controls (n = 10). Data were collected via semi-structured telephone interviews upon enrollment and 1 month after enrollment or attendance at a COACH program session. Results: The results revealed significant differences in knowledge from pre- to postassessment between the pilot and control samples ( P = .02). Although no other statistically significant between-group differences were found, paired-sample t tests revealed significant pre–post increases in transplant knowledge (7.6 [standard deviation, SD = 2.0] to 9.5 [SD =1.8]; P = .05) and communication self-efficacy (1255.8 [SD = 239.7] to 1513.8 [SD = 114.3]; P = .009) for pilot participants. Decreases in perceived conversational difficulties were also observed ( P = .53). Discussion: Results provide preliminary support for the program's impact. Moreover, participant evaluations of the COACH were overwhelmingly positive. A more definitive program evaluation with a larger, more diverse sample is currently underway.